Causes of false‐negative sentinel node biopsy in patients with breast cancer. Issue 6 (22nd February 2013) - Andersson, Y.; Frisell, J.; Sylvan, M.; de Boniface, J.; Bergkvist, L.
<x xml:space="preserve">Abstract</x> Background Sentinel lymph node (SLN) biopsy has replaced axillary lymph node dissection as the routine staging procedure in clinically node‐negative breast cancer. False‐negative SLN biopsy results in misclassification and may cause undertreatment of the disease. The aim of this study was to investigate whether serial sectioning of SLNs reveals metastases more frequently in patients with false‐negative SLNs than in patients with true‐negative SLNs. Methods This was a case–control study. Tissue blocks from patients with false‐negative SLNs, defined as tumour‐positive lymph nodes excised at completion axillary dissection or a subsequent axillary tumour recurrence, were reassessed by serial sectioning and immunohistochemical staining. For each false‐negative node, two true‐negative SLN biopsies were analysed. Tumour and node characteristics in patients with false‐negative SLNs were compared with those in patients with a positive SLN by univariable and multivariable regression analysis. Results Undiagnosed SLN metastases were discovered in nine (18 per cent) of 50 patients in the false‐negative group and in 12 (11.2 per cent) of 107 patients in the true‐negative group (P = 0.245). The metastases were represented by isolated tumour cells in 14 of these 21 patients. The risk of a false‐negative SLN was higher in patients with hormone receptor‐negative (odds ratio (OR) 2.50, 95 per cent confidence interval 1.17 to 5.33) or multifocal tumours (OR 3.39, 1.71 to 6.71), or if only one SLN was identified (OR 3.57, 1.98 to 6.45). Conclusion SLN serial sectioning contributes to a higher rate of detection of SLN metastasis. The rate of upstaging of the tumour is similar in false‐ and true‐negative groups of patients.